ASSESSMENT THE MICROBIAL CONTAMINATION OF MOBILE PHONE AMONG HEALTH CARE WORKERS IN AZADI TEACHING HOSPITAL KIRKUK / IRAQ - Mohammad khedher Abdulwahd; Zahraa Ahmed Hassan; Asmaa O.namuq (Scholar Express Journals, 2022)
The goal of this study was to adopt a comprehensive approach to understanding nucleic acids' reality and function in the body of the organism, in addition to their biological and chemical characteristics. For all living things, nucleic acids serve as essential macromolecules or biological polymer components. They are made up of nucleotide-based units or monomers. Phosphate group, nitrogenous base, and ribose sugar make up each of their three constituent elements. Generally speaking, there are just two essential types of nucleic acids. If the sugar is the ribose derivative deoxyribose, the polymer is (DNA) or deoxyribonucleic acid, and if the sugar is ribose, the polymer is (RNA) or ribonucleic acid. In actuality, the basic informationcarrying molecules in cells, known as nucleic acids or genetic materials, are chemical substances. Friedrich Miescher, a scientist, was the first to discover and identify nucleic acids, naming them nuclein, while Watson and Crick proposed the double-helix structure of DNA. In this regard and historically speaking.
Keywords: Definition of DNA; structure; function and replication